Diameter Increment of Terminalla Paniculata and Lagerstroemia lanceolata - Rai, S. N. (Indian Forester, 1980)
A knowledge of rate of diameter growth is of vital importance in forest management. This growth can be studied in sample plots, where trees are permanently numbered and their measurement is recorded, periodically. In this study rate of diameter increment of Terminalia paniculata Roth. And Lagerslroemia lanceolata Wall. Has been determined from the data of eight sample plots, existing in Southern Tropical Moist Deciduous Forests of Karnataka State, India. The d b h (ob) and rate of periodic diameter increment (5 years in this case) has been used to fit in a regression equation. The model used is : Y = a + b X + CX2 Where Y = Periodic diameter increment in cm, X = Diameter b h (ob) in cm. and 'a', 'b', 'c' arc constants. Equation for both the species is given. With the help of the above equation, Age/DBH curve for the two species has been constructed. In the locality Terminalia paniculata and Lagerslroemia lanceolata take 203 and 201 years, respectively, to reach a d b h (ob) of 60 cm.